Etapy tworzenia informacji radiowej - Świętosławski, Michał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
Who? What? Where? When? Why? – a journalist who is preparing the news always must find the answers on those questions. The information must be interesting, surprising and sometimes even shocking. I try to show you what are the stages of preparing radio news.